Consumer Flow Experience of Senior Citizens in Using Social Media for Online Shopping - Xu, Ying; Wang, Yixuan; Khan, Asif; Zhao, Ranlin (Frontiers in Psychology, 2021)
Senior market signifies an enormous, rapidly expanding segment, this research investigates this segment by proposing a theoretical model incorporating the antecedents of consumer flow experience, flow theory, and technology acceptance model (TAM) devised for determining social media purchase intention. This study focuses on the senior citizens engaged in shopping using social media located in Pakistan. A total of 300 senior citizens were selected. An online survey was conducted with the help of a marketing research agency located in Pakistan. The data were analyzed using the partial least square method. According to the results, the antecedents including feedback, enjoyment, and time distortion were found to be in a positive relationship with flow experience, however, concentration did not have a significant effect on flow. Furthermore, the flow was found to be in a significant relationship with social media purchase intention and TAM. Finally, TAM was also found to be in a positive significant relationship with social media purchase intention. This research contributes to the constantly expanding volume of the senior market segment population’s utilization of social media for buying producing highly valuable knowledge for manufacturers, wholesalers, vendors, and a huge number of senior customers.